A new aetosaur from the Upper Triassic of the Santa Maria Formation, southern Brazil - Roberto-Da-Silva, Lúcio; Desojo, Julia B.; Cabreira, Sérgio F.; Aires, Alex S. S.; Müller, Rodrigo T.; Pacheco, Cristian P.; Dias-Da-Silva, Sérgio (Zootaxa, 2014)
Aetosaurs are armored pseudosuchian archosaurs widespread in Upper Triassic units. In South America, four taxa were previously recorded: Aetosauroides scagliai, Neoaetosauroides engaeus, Aetobarbakinoides brasiliensis, and Chilenosuchus forttae. Herein we describe a new Late Triassic juvenile aetosaur from the Santa Maria Formation of southern Brazil, Polesinesuchus aurelioi gen. et sp. nov., increasing the paleobiodiversity of this interesting group to five taxa in Western Gondwana. The holotype is composed of cranial (parietal and braincase) and postcranial elements (cervical, dorsal, sacral, caudal vertebrae, both scapulae, a humerus, ilium, pubis, ischium, tibia, a partial right pes, and anterior and mid-dorsal paramedian osteoderms). It belongs to a juvenile individual, as its neurocentral sutures are open in all vertebrae, and also due to its small size. However, future paleohistological investigation is necessary to fully corroborate this assumption. This new taxon is distinguished from all other aetosaurs by the presence of an unique combination of character states (not controlled by ontogeny) such as: cervical vertebrae with prezygapophyses widely extending laterally through most of the anterior edge of the diapophyses; absence of hyposphene articulations in both cervical and mid-dorsal vertebrae; presence of a ventral keel in cervical vertebrae; anterior and mid-dorsal vertebrae without a lateral fossa in their centra; expanded proximal end of scapula; anteroposteriorly expanded medial portion of scapular blade; a short humerus with a robust shaft; and a dorsoventral and very low iliac blade with a long anterior process which slightly exceeds the pubic peduncle. Regarding its phylogenetic relationships, the present analysis placed Polesinesuchus as the sister taxon of Aetobarbakinoides and both as sister taxa of the unnamed monophyletic clade Desmatosuchinae plus Typothoracisinae.